Instilling the Values of Tawhid Through Islamic Counseling Services in Islamic Boarding Schools - Munir, Kader; Lubis, Saiful Akhyar; Arsini, Yenti (Fitrah: Journal of Islamic Education, 2025)
The cultivation of monotheistic values in pesantren plays an important role in shaping the character and spirituality of santri. However, in the midst of the times influenced by globalization and modernization, the cultivation of the value of monotheism faces various challenges. This study aims to analyze the values of monotheism given to santri through Islamic counseling services, the implementation of the cultivation of monotheistic values, supporting and inhibiting factors, and efforts to overcome these obstacles in Langkat Regency Islamic Boarding Schools. The method used is qualitative with a multisite approach, which allows comparison of two pesantren to obtain a comprehensive understanding. The results showed that the values of tawheed taught included the tawheed of Rububiyah, Uluhiyah, and Asma wa Sifat. The implementation of instilling the value of tawhid is carried out through a systematic curriculum and varied methods. The main supporting factors include competent teaching, a religious environment, and family support. However, the influence of globalization and technology is a major challenge. Efforts to overcome obstacles involve integrating theory with worship practices, personal mentoring, and utilizing technology in learning. This study suggests the importance of cooperation between pesantren, families, and communities to support the internalization of the values of monotheism.